Absorption and emission features of 7Be ii in the outburst spectra of V838 Her (Nova Her 1991). Issue 2 (23rd August 2018) - Selvelli, P; Molaro, P; Izzo, L
ABSTRACT: High- and low-resolution International Ultraviolet Explorer ( IUE ) spectra of V838 Her in the early outburst stages exhibit a strong absorption feature shortward of λ3130. We discuss the nature of this spectral feature and provide convincing evidence that it corresponds to the blueshifted resonance doublet of singly ionized 7 Be recently discovered in other novae. During the evolution of the outburst the appearance of an emission feature close to λ3130 Å is also identified as 7 Be ii λ3132 because the usual identification as the O iii λ3133.7 Bowen fluorescence line is hardly compatible with both the known oxygen underabundance in the nova ejecta and the low optical depths in the nebula due to the high outflow velocity. The average 7 Be abundance relative to hydrogen, estimated by four different methods, i.e. the 7 Be ii /Mg ii absorption ratio, and the 7 Be ii /Mg ii, 7 Be ii /He ii 1640, and 7 Be ii /Hβ emission ratios, is N (Be)/ N (H) ≈2.5 × 10 −5 (by number), i.e. ≈1.7 × 10 −4 by mass. This corresponds to an overproduction of 7 Be by about 1 dex in comparison with the theoretical models of massive CO and ONe novae. Since 7 Be all converts into 7 Li, the 7 Be/H abundance implies a 7 Li/H overabundance of about 4 dex over the 7 Li/H meteoritic value and indicates a total ejected mass of 7 Li of ≈9.5 × 10 −10  M$\odot$ . These data are in line with previous observations and indicate that large amounts of 7 Li can be synthesized in a variety of novae, including very fast ONe novae.